Learning preferences and entry mode as predictors of students’ academic performance in higher institutions of learning - Jumoke Iyabode Oladele (Universitas Negeri Padang, 2023)
The aim of the study was to examine entry mode and study ethics as predictors of student academic achievement among university undergraduates in a Nigerian University. The study employed the correlation research design in the quantitative approach. Purposive sampling technique was used to draw a sample of 154 students out of which 128 students consented and participated in the study. The instrument for the study was a researcher designed questionnaire which was piloted and subjected to a test of internal consistency, using Cronbach's alpha reliability analysis, and the overall reliability coefficients of 0.71 was obtained. The questionnaire was administered to the respondents through online mode using Google form. The data was gathered within a period of three (3) weeks. A WhatsApp research group was created through which the google form link was shared for effective dissemination. Data was collected was analyzed using descriptive statistic of frequency and percentage to present the respondents demographic information of respondents while mean and standard deviations was used to answer research questions The study hypothesis was tested using multiple regression using Statistical Package for Social Sciences (SPSS) 29.0. The study findings revealed that students learning preferences significantly predicted their academic achievement based on which a conclusion were made. The development of policies, programs, and initiatives aimed at improving educational outcomes and enhancing the overall quality of higher institutions of learning was recommended among others.